Measurement Error in Education and Growth Regressions - Miguel Portela; Rob J. M. Alessie; Coen N. Teulings (Center for Economic Studies and ifo Institute (CESifo), 2006)
The perpetual inventory method used for the construction of education data per country leads to systematic measurement error. This paper analyses the effect of this measurement error on GDP regressions. There is a systematic difference in the education level between census data and observations constructed from enrolment data. We discuss a methodology for correcting the measurement error. The standard attenuation bias suggests that using these corrected data would lead to a higher coefficient. Our regressions reveal the opposite. We discuss why the measurement error yields an overestimation. Our analysis contributes to an explanation of the difference between regressions based on 5 and on 10 year first-differences.
Keywords: O4; I2; 330; growth; education; measurement error; Bildung; Bildungsniveau; Messung; Wirtschaftswachstum; Schätzung; Statistischer Fehler; Regression; Theorie; Welt